EVALUATION OF OKRA AND SEBESTAN FRUITS AS A BINDERS IN THE DIETS OF BUNNI (BARBUS SHARPEYI) - MAHDI, A.A.; AL-DUBAKEL, A.Y.; ESAHA, J.M.; ABDUL, S.M. (Iraqi Journal of Aquaculture, 2022)
Okra (Abelmoschus esculentus) and Sebestan (Cordia myxa) fruits were used as plant binders in the diets of Bunni (Barbus sharpeyi) . These binders were beside a control diet without binder., compared with the starch as a traditional binders.All binders included in the diets by 2% were with two replicates for each treatments. Feeding rate was 4% of fish weight for 70 days. The physical properties of diets showed that the control diet has the highest density while the diet containing starch has the lowest followed by Okra and Sebestan. Bouncy was 25 Sec. while 34 min. needed for dissolving for Okra diet compared to one sec. and two min. for control respectively The later diet showed 60 % for splitting .The chemical composition of diets was not affected by adding the binders as well as palatability of diets as high values were recorded in weight increments , relative and specific growth rates in experimented diets .Moreover the chemical composition of fish was not affected after feeding compared to those before it. The present study revalid the possibility of using some plant materials especially Okra as fish diets binder.